FACTORS INFLUENCING TECHNOLOGY ADOPTION IN LOGISTICS MANAGEMENT: SYSTEMATIC LITERATURE REVIEW TO OPTIMIZE DIGITAL TRANSFORMATION - Permata, Wahyu Indra; Maniah, Maniah (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Digital transformation in the logistics sector is increasingly important to improve the efficiency, speed, and accuracy of services in the global supply chain. However, the adoption of technology in logistics management still faces various challenges, both from the internal side of the organization and external factors. This study aims to identify and analyze the factors influencing the adoption of technology in logistics management through a systematic literature review (SLR) approach. The method used involves the collection and critical analysis of 60 scientific articles published in the period 2018 to 2024 from various reputable databases. The results show that factors such as technology readiness, human resource competence, top management support, external pressures, and relative benefits of technology are highly influential in the adoption process. The discussion further outlined how the integration of these factors can accelerate digital transformation and increase the competitiveness of logistics companies. The study concludes that a strategic approach that considers technical, organizational, and environmental aspects is essential to drive successful technology adoption. It is recommended that logistics companies actively evaluate the readiness of the internal and external environment before implementing new technologies and use the results of this study as a reference in strategic decision-making in the field of logistics digitalization